Heroes Without a Cape: The Romanticization and Fail in Comunication with Healthcare Workers in The COVID-19 Pandemic - Merino-Jaramillo, Grace; Trujillo-Montalvo, Patricio (International Journal of Membrane Science and Technology, 2023)
In December 2019 in the Chinese city of Wuhan, Hubei province, health systems reported patients affected by atypical pneumonia of unknown origin, the disease was identified as SARS-CoV-2, a new virus of the Coronaviridae family, The COVID-19, and it appeared suddenly generating a global crisis, with serious effects on economies and health systems. To describe the feelings and perceptions of a group of health workers, whom in Ecuador, the government, using the media, romanticized, placing them at the level of heroes without a cape who faced the pandemic in the front line. This article presents testimonies that narrate the experiences of human beings strongly marked by closeness to death, the feeling of loss, powerlessness and guilt, since their effort, work, experience and training were not enough to save the lives of critically ill patients of COVID-19. Health workers were romanticized as heroes but at the same time precarious, they received little bio-security protection, which increased infections and deaths at the level of health personnel. The negative impact of COVID 19 at the psychosocial level and the effects on the mental health of health workers is a poorly studied issue; work should be done to better understand the perceptions of frustration, fear, stress and social stigma than many health workers did. They felt by being potential carriers of the virus and taking it to their close environments.